A Muscovite Republic?. Issue 3 (2021) - Kollmann, Nancy Shields
Abstract : A response to Oleg Khakhorin's stimulating application of Anthony Kadellis' "The Byzantine Republic" to Russian history, this article explores the fundamental features of Muscovite political culture.